2014
DOI: 10.1002/bip.22526
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glycosylation on the antibody recognition of a MUC2 mucin epitope

Abstract: MUC2 glycoprotein, produced by the epithelium of the colon and built up mainly of repeat units of (1) PTTTPITTTTTVTPTPTPTGTQT(23) , can be overexpressed or underglycosylated in gastrointestinal diseases, e.g. in case of colon carcinoma. We have been studying the epitope structure of the MUC2 by focusing on the repeat unit with the mucin peptide specific MAb 996 monoclonal antibody. This antibody recognizes the (18) PTGTQ(22) sequence as minimal, and (16) PTPTGTQ(22) as optimal epitope within the underglycosyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…However, when we used the CE result to calculate the product yield we found 6.1 ± 0.1 mg/L of viscumin heterodimer in the elution fraction corresponding to 7.2 ± 0.1 mg/kg fresh leaf biomass (AM ± SD, n = 2) and a purity of 0.54 g/g TSP (Table ). We concluded that the direct CE‐derived yield and purity seemed more likely than the ~1.2 mg/kg and 0.08 g/g, respectively determined by the indirect SPR assay (Figure S2), because the latter can be affected by differential glycosylation patterns of proteins (Uray, Mizuno, Inazu, Goto, & Hudecz, ). For example, epitope recognition and binding kinetics of mAbs can differ for glycosylated and nonglycosylated products.…”
Section: Resultsmentioning
confidence: 96%
“…However, when we used the CE result to calculate the product yield we found 6.1 ± 0.1 mg/L of viscumin heterodimer in the elution fraction corresponding to 7.2 ± 0.1 mg/kg fresh leaf biomass (AM ± SD, n = 2) and a purity of 0.54 g/g TSP (Table ). We concluded that the direct CE‐derived yield and purity seemed more likely than the ~1.2 mg/kg and 0.08 g/g, respectively determined by the indirect SPR assay (Figure S2), because the latter can be affected by differential glycosylation patterns of proteins (Uray, Mizuno, Inazu, Goto, & Hudecz, ). For example, epitope recognition and binding kinetics of mAbs can differ for glycosylated and nonglycosylated products.…”
Section: Resultsmentioning
confidence: 96%
“…Additional evidence of the enzyme treatment was the reduction in all of the EV markers analyzed (i.e., CD9, CD63, CD90), indicating the presence of sensitive epitopes for PNGase-F. In fact, the antibody-binding alterations due to glycosylation were already reported [ 52 , 53 ]. The high diversity of the glycans affected by PNGase-F treatment precluded any identification of the specific targets involved in the analyzed functions.…”
Section: Discussionmentioning
confidence: 91%
“…This is the case of the α2,3-SA PSA glycoforms for prostate cancer [ 72 ], core fucosylated-AFP glycoforms (AFP-L3) for hepatocellular carcinoma [ 73 ] or CA125-STn for ovarian cancer [ 74 ]. In addition, this knowledge could be useful for therapies targeting MSLN using specific antibodies [ 28 , 41 ], because their affinity could be dependent on the type of MSLN glycans, as it has been described for other glycoproteins [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%